The Association between Fetal Fibronectin, Cervical Length, and Amniotic Fluid Sludge with Histological Indicators of Placental Inflammation in Twin Gestations - Ayodele, Aboluwade; Fox, Nathan S.; Gupta, Simi; Spiegelman, Jessica; Saltzman, Daniel H.; Booker, Whitney; Rebarber, Andrei (American Journal of Perinatology, 2018)
Objective The objective of this study was to evaluate the association of screening tests for preterm birth (short cervical length [CL], positive fetal fibronectin (FFN), and amniotic fluid [AF] sludge) in twin gestations with histologic evidence of placental inflammation.Study Design Historical cohort study of 596 twin gestations delivered in a single maternal–fetal medicine practice with CL and FFN testing from 22 to 256/7 weeks. A short CL was defined as ≤25 mm. Placental lesions evaluated were chronic and acute membrane inflammation and funisitis. Fischer's exact test and logistic regression were used.Results None of the screening tests was associated with chronic inflammation. All were associated with acute inflammation. On regression analysis, a short CL and positive FFN remained independently associated with acute inflammation (adjusted odds ratio [aOR]: 5.66 and 2.51, respectively) and funisitis (aOR: 5.66 and 7.17, respectively). AF sludge was not independently associated with acute inflammation nor funisitis.Conclusion In twin gestations, a short CL and a positive FFN at 22 to 26 weeks are associated with acute but not chronic inflammation on placental histology. These findings imply that mechanisms underlying preterm birth in twins that result in positive screening tests weeks prior to delivery are not reflected as chronic placental inflammation. Therefore, pathologic interpretation of etiologic mechanisms for preterm birth may be limited using solely histologic reports.
Keywords: twin gestations; placental histology; cervical shortening; fetal fibronectin